An unusual pulmonary mycobacterial infection: Case report and literature review - Catriona Macrae; Nicholas Kennedy (Clinical Infection in Practice)
Non-tuberculous mycobacteria (NTM) are mycobacterial species other than Mycobacterium tuberculosis complex (MTB) and the organisms that cause leprosy. They can cause pulmonary, central nervous system, lymph-node, joint, catheter-related as well as disseminated infection. NTM pulmonary disease (NTM-PD) occurs when NTM infection causes progressive inflammatory lung damage. NTM-PD is increasing in both incidence and prevalence. Mycobaterium szulgai, is an uncommon, slow-growing NTM. M. szulgai primarily causes pulmonary infections which present like MTB pulmonary infections. Due to low prevalence there are no standardised treatment guidelines for the management of M. szulgai infection.We describe a case of M. szulgai pulmonary infection in diabetic man in his fifties who presented with productive cough, dyspnoea, weight loss, fatigue and night sweats. Computed tomography (CT) showed three thick walled cavities in the right lung, with consolidation, emphysema and adenopathy, thought to be reactive. Sputum samples were positive for acid alcohol fast bacilli (AAFB) but MTB PCR testing was negative. Sputum culture grew M. szulgai. He was treated with on Rifampicin, Isoniazid, Ethambutol and Azithromycin for 13 months. The patient improved significantly following initiation of anti-mycobacterial treatment.The patient’s clinical presentation, radiological findings of upper lobe cavitating lesions, and characteristics; male, over 50 years old, immunosuppressed with underlying lung disease, are similar to most reported cases. M. szulgai can rarely infect immunocompetent hosts. Evidence to guide therapy is lacking. Treatment duration in the literature varies from six months to 39 months. Resistance to isoniazid has been reported and an isolate with both rifampicin and ethambutol resistance documented. Consensus guidelines recommend that NTM should be treated for at least 12 months from the first negative sputum culture. A combination of at least three susceptible drugs should be used, with rifampicin, ethambutol and azithromycin or clarithromycin recommended first line.